Digitalization and Retail Sector Productivity in Bulgaria - Dimitrova, Violeta (Research Papers, 2021)
The widespread penetration of digitalization changes the nature of exchange between market agents and has a direct impact on the forms of trade, including retail. The aim of this study is to examine the productivity of retail trade in the context of digitalization based on a brief theoretical analysis and the example of empirical data from the retail sector in Bulgaria for the period 2008 – 2019 or between the two economic crises. A descriptive analysis was used. Productivity is presented as the ratio of gross value added, volume of sales and gross income per employee.
Keywords: Retailing; Productivity; Digitization; Gross margin